Institutionalization of the national idea in the context of globalization and its socio-philosophical foundations (Zien Journal of Social Sciences and Humanities, 2022)
This article analyzes the development of Uzbekistan at a new stage of development and its connection with the national idea, the fact that the national idea is an important factor in the development of society.